Apparent and Measured Rates of Nitrification in the Hypolimnion of a Mesotrophic Lake - Hall, Grahame H. (1982)
Three distinct phases were observed in the change of dissolved inorganic nitrogen concentrations in the hypolimnion of Grasmere. The second phase of decreasing ammonia and increasing nitrate concentrations was typical of the nitrification process. Observations on nitrate concentration gradients between surface sediments and the water column and experiments using the nitrification inhibitor N-Serve indicated the in situ activity of chemolithotrophic nitrifying organisms. Nitrification rates were estimated throughout the period of stratification by using the N-Serve and [(14)C]bicarbonate uptake method. Comparison of the field nitrate concentrations with the predicted nitrate concentrations (from estimates of the nitrification rate) indicated that the method underestimated the true rate of nitrification. Possible reasons for this are discussed.